DATA DRIVING TYPE DATA PROCESSOR - MIURA HIROKI (1990)
PURPOSE:To completely prevent a queue memory from being overflowed due to data forming processing without remarkably increasing the number of hardwares by providing the subject processor with a data volume monitoring means for monitoring data volume stored in the queue memory and a formation processing inhibiting flag. CONSTITUTION:The queue memory Q is collectively held in one position and the processor is also provided with the data volume monitoring means for monitoring data volume in the queue memory Q and a program storing means PM for storing program information including the connecting information of a data flow graph and forming and outputting one or plural new data obtained by updating the control information of an arriving data into new control information in accordance with the arrival of the data. Consequently, the queue memory Q can be completely prevented from overflowing without remarkably increasing the number of hardwares.